Innovating Cybersecurity in Tanzanian Academia: A Mobile Tool for Combatting Social Engineering Threats - Mjema, Lucas Hosea; Mgawe, Bonny Said; Dida, Mussa Ally (Universitas Bina Darma, 2025)
Social engineering attacks, including phishing, smishing, and vishing, pose significant threats to higher learning institutions, especially in regions with limited cybersecurity awareness and weak incident reporting mechanisms. This study introduces a novel mobile tool that combines real-time threat detection, streamlined reporting, and personalized training to address these vulnerabilities. Using a mixed-methods approach, we gathered survey data from 395 participants, conducted interviews with 10 IT professionals, and ran a pilot test with 20 users. The proposed tool provides instant scanning of emails/SMS for social engineering content and instant incident reporting alongside interactive, bilingual (English/Swahili) training modules. Results show a substantial improvement in user awareness, 85% of users reported a better understanding of social engineering threats after using the app, and high user satisfaction, with 90% expressing approval of the intuitive interface. The integration of real-time threat analysis and immediate reporting with tailored education distinguishes our tool from existing solutions. We discuss how bilingual support broadened engagement and how personalized learning paths reinforced retention of security best practices. Our findings demonstrate that a mobile-based, user-centric approach can significantly bolster cybersecurity awareness and incident response in academic environments. Future work will integrate machine learning for enhanced threat detection and voice-guided features for accessibility, aiming to continuously adapt to evolving attack strategies. This research provides insights for policymakers on incorporating such tools into broader institutional cybersecurity strategies.